Feasibility and role of echocontrast evaluation of patients with LVAD. (4th February 2022) - Baroni, G; Pergola, V; Semeraro, L; Mastro, F; Dellino, C; Aruta, P; Cecchetto, A; Previtero, M; Florencis, A; Tarzia, V; Mele, D; Gerosa, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with Advanced heart failure (AHF) long-term support with durable mechanical circulatory support (MCS) devices such as left ventricular assist device (LVAD) brings survival benefits and improvement in quality of life, compared with conventional medical treatments. Development of RVF in patients with LVAD has a direct effect on mortality and is associated with prolonged length of stay in intensive care unit and in-hospital stay and with poor quality of life. Purpose: the evaluation of clinical safety and feasibility of echocontrast (EC) in patients implanted with 3 different types of LVAD (HeartWAre HVAD, Jarvik 2000, HeartMate 3); the assessment of the improvement in the visualization of heart structures; the intra and inter-operator agreement of RV measurements (FAC, TAPSE, sPAP, TR, regional wall motion abnormalities) with and without contrast. Methods: Between 2014 and 2019, 43 patients were implanted with LVAD, in particular 7 (16%) patients were implanted with Jarvik 2000, 31 (72%) with HeartMAte 3, 5 (12%) pts with HeartWAre HVAD. Nine patients (21%) either had contraindication or refused contrast injection. In 3 (7%) patients, it was technically challenging to obtain apical images at all levels. Two (5%) patients lost their follow-up. Our final population was of 29 (67%) patients. We also assessed the reproducibility of these measurements between two different expert operators (blind analysis). Results: We observed no allergic reaction to EC. Total 329 (64%) of 516 RV wall segments were available for qualitative analysis without contrast vs 451 (87%) with contrast (p < 0.001) with a significant improvement of the evaluability of regional contractility and FAC (41% vs 90%, p < 0.001). Evaluation of TAPSE, TR and sPAP was similar with and without contrast (p = NS) All the RV parameters showed little inter-operator variability when measured with contrast. TAPSE, FAC, and RWMA showed an excellent reproducibility (ICC >0.86) while it was good for 2D-baseline derived parameters (ICC = 0.74) showing improvement of inter operator reproducibility in the evaluation of regional contractility in the contrast echocardiography modality. Conclusion: EC is safe with all the types of LVAD we examined. Accurate and reproducible visualization of RV is imperative for reliability of information, a routine use of EC could play a pivotal role in interpreting RV features. EC improves RV morphologic and functional judgment; allowing greater accuracy and precision in the assessment of both global and regional RV functions. This finding may have important clinical improvement, especially in the future for analysis focused in RV prognostic role in LVAD patients